An analysis of the epistemic link between the Catholic religion and violence in Uganda's history - Kizito, Kiyimba (Academy of Science of South Africa, 2017)
Uganda’s recent history of violence has had an interesting characteristic: it has arguably been mainly within the Christian and more specifically Catholic religious space. I examine four cases of religious-related violence in order to cipher the epistemic roots of such violence. The four cases are: the Uganda Martyrs; Ms Alice Lakwena and the Holy Spirit Movement; Mr Joseph Kony and the Lord’s Resistance Army; and Ms Ceredonia Mwerinde and the Movement for the Restoration of the Ten Commandments of God. I examine the literature critically in order to test the plausibility of various positions on the possible link between the Catholic religion and violence in Uganda. My analysis looks at the links both from the point of view of the perpetrators of violence and the adherent/victims of the violence. In the end, I find that the epistemic links are more justificatory/explanatory than they are causal.